2019
DOI: 10.1111/pbi.13117
|View full text |Cite
|
Sign up to set email alerts
|

A directed learning strategy integrating multiple omic data improves genomic prediction

Abstract: Summary Genomic prediction (GP) aims to construct a statistical model for predicting phenotypes using genome‐wide markers and is a promising strategy for accelerating molecular plant breeding. However, current progress of phenotype prediction using genomic data alone has reached a bottleneck, and previous studies on transcriptomic and metabolomic predictions ignored genomic information. Here, we designed a novel strategy of GP called multilayered least absolute shrinkage and selection operator (MLLASSO) by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 43 publications
(68 reference statements)
1
27
0
Order By: Relevance
“…This makes it possible to uncover genotype-phenotype relationships using different types of data. Related studies were reported using omics data to perform genomic prediction for complex traits in humans [19,20], plants [21][22][23][24], and model animals [25,26]. Most of these studies focused on integrating multiple omics data into a prediction model to improve prediction accuracy [22,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…This makes it possible to uncover genotype-phenotype relationships using different types of data. Related studies were reported using omics data to perform genomic prediction for complex traits in humans [19,20], plants [21][22][23][24], and model animals [25,26]. Most of these studies focused on integrating multiple omics data into a prediction model to improve prediction accuracy [22,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Both this study and several previous studies have indicated that integrating transcriptomic data into genomic prediction is a feasible method to improve the power of genomic prediction (Azodi et al, 2019;Hu et al, 2019;Morgante et al, 2019).…”
Section: Challenges For Integrating Transcriptomic Data Into Genomic mentioning
confidence: 71%
“…Related studies were reported using omics data to perform genomic prediction for complex traits in humans (Vazquez et al, 2016;Dimitrakopoulos et al, 2017), plants (Xu et al, 2017;Azodi et al, 2019;Hu et al, 2019;Wang et al, 2019), and model animals (Li et al, 2019;Morgante et al, 2019). Most of these studies focused on integrating multiple omics data into a prediction model to improve prediction accuracy (Guo et al, 2016;Xu et al, 2017;Li et al, 2019;Morgante et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Omics data started to be integrated into the genomic selection models. For example, transcriptomic and metabolomic data have been combined into genomic selection to boost the power of prediction (Hu et al 2019). Additionally, by incorporating evolutionary information into the genomic selection model, the prediction accuracy has been improved for up to 4% for yield-related traits in maize (Yang et al 2017).…”
Section: )mentioning
confidence: 99%